Pemberdayaan Petani Buah Naga Desa Nusa Makmur Kecamatan Air Kumbang Kabupaten Banyuasin - Wulansari , Febrisa; Suryati, Suryati; Muzaiyanah, Muzaiyanah (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This thesis is entitled "Empowering Dragon Fruit Farmers in Nusa Makmur Village, Air Kumbang District, Banyuasin Regency." The purpose of this study is to find out what the benefits of dragon fruit are for people's lives in Nusa Makmur Village, to find out the strategies for empowering dragon fruit in Nusa Makmur Village, Air Kumbang District, Banyuasin Regency. The research method used in this thesis is a qualitative method, researchers used informants from dragon fruit orchard owners and dragon fruit farmers in Nusa Makmur Village, Air Kumbang District, Banyuasin Regency. Collecting data in this study using interviews, observation, documentation and data analysis techniques used in this study, namely data reduction, data presentation and drawing conclusions. The results obtained from this study, firstly the benefits of dragon fruit for the life of the people in Nusa Makmur Village are that it can improve the economy of the people of Nusa Makmur village with the existence of a dragon fruit orchard that can help increase the income of the village community and for health it can help repair and restore loss of appetite, help in lowering bad cholesterol levels, besides that dragon fruit can be processed back into juice, jam, natural red dye, and jelly and many other benefits.